Phase modulation and amplitude modulation interconversion for magnonic circuits - Tock, C; Gregg, J (American Physical Society, 2019)
Magnonic circuit elements generally operate using signals that are either amplitude or phase modulated. We propose a simple all-magnon circuit element capable of converting between these two types of encoding, and support our design with simulations. We highlight the potential of our technique to augment existing devices and propose an alternative schematic for an “equality” gate and exclusive nor gate.